2020
DOI: 10.30684/etj.v38i5a.519
|View full text |Cite
|
Sign up to set email alerts
|

Extract the Similar Images Using the Grey Level Co-Occurrence Matrix and the Hu Invariants Moments

Abstract: In the last years, many types of research have introduced different methods and techniques for a correct and reliable image retrieval system. The goal of this paper is a comparison study between two different methods which are the Grey level co-occurrence matrix and the Hu invariants moments, and this study is done by building up an image retrieval system employing each method separately and comparing between the results. The Euclidian distance measure is used to compute the similarity between the query image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The accuracy of this method to identify wood knots reaches 92.80%. In 2020, Beshaier and Yossra et al conducted a comparative study on two different image retrieval methods of gray level co-occurrence matrix (GLCM) and Hu invariant moments [19]. The results showed that the average accuracy of GLCM and Hu invariant moments is 92.8% and 84.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of this method to identify wood knots reaches 92.80%. In 2020, Beshaier and Yossra et al conducted a comparative study on two different image retrieval methods of gray level co-occurrence matrix (GLCM) and Hu invariant moments [19]. The results showed that the average accuracy of GLCM and Hu invariant moments is 92.8% and 84.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%